Effect of glycemic control on the risk of pancreatic cancer: A nationwide cohort study. Issue 24 (June 2016) - Er, Kian-Ching; Hsu, Chen-Yang; Lee, Yi-Kung; Huang, Ming-Yuan; Su, Yung-Cheng
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Although the relationship between diabetes and pancreatic cancer has been studied, the effects of glycemic control on pancreatic cancer have never been evaluated. This study investigates the relationship between glycemic control and pancreatic cancer. Data from 1 million National Health Insurance beneficiaries were screened. The study cohort consisted of 46, 973 diabetic patients and 652, 142 nondiabetic subjects. Of the patients with diabetes, 1114 who had been admitted for hyperglycemic crisis episodes were defined as having poorly controlled diabetes. All adult beneficiaries were followed from January 1, 2005 to December 31, 2013, to determine whether pancreatic cancer was diagnosed. The Cox regression model was applied to compare the adjusted hazards for potential confounders. After controlling for age, sex, urbanization level, socioeconomic status, chronic liver disease, hypertension, coronary artery disease, hyperlipidemia, malignancies, smoking, chronic obstructive pulmonary disease, obesity, history of alcohol intoxication, chronic renal insufficiency, biliary tract disease, chronic pancreatitis, Charlson Comorbidity Index score, and high-dimensional propensity score, the adjusted hazard ratio of pancreatic cancer was 2.53 (95% confidence interval 1.96–3.26) in patients with diabetes. In diabetic patients with poor glycemic control, the hazard ratio of pancreatic cancer was significantly higher (hazard ratio 3.61, 95% confidence interval 1.34–9.78). This cohort study reveals a possible relationship between diabetes and pancreatic cancer. Moreover, poorly controlled diabetes may be associated with a higher possibility of pancreatic cancer.